DnmA and FisA Mediate Mitochondria and Peroxisome Fission, and Regulate Mitochondrial Function, ROS Production and Development in Aspergillus nidulans - Garrido-Bazán, Verónica; Pardo, Juan Pablo; Aguirre, Jesús (Frontiers in Microbiology, 2020)
The dynamin-like protein Drp1 and its receptor Fis-1 are required for mitochondria and peroxisome fission in animal and yeast cells. Here, we show that in the fungus Aspergillus nidulans the lack of Drp1 and Fis-1 homologs DnmA and FisA has strong developmental defects, leading to a notable decrease in hyphal growth and asexual and sexual sporulation, with some of these defects being aggravated or partially remediated by different carbon sources. Although both DnmA and FisA, are essential for mitochondrial fission, participate in peroxisomal division and are fully required for H2O2-induced mitochondrial division, they also appear to play differential functions. Despite their lack of mitochondrial division, dnmA mutants segregate mitochondria to conidiogenic cells and produce viable conidia that inherit a single mitochondrion. During sexual differentiation, dnmA and fisA mutants develop fruiting bodies (cleistothecia) that differentiate excessive ascogenous tissue and a reduced number of mostly non-viable ascospores. dnmA and fisA mutants show decreased respiration and notably high levels of mitochondrial reactive oxygen species (ROS), which likely correspond to superoxide. Regardless of this, dnmA mutants can respond to an external H2O2 challenge by re-localizing the MAP kinase-activated protein kinase (MAPKAP) SrkA from the cytoplasm to the nuclei. Our results show that ROS levels regulate mitochondrial dynamics while a lack of mitochondrial fission results in lower respiration, increased mitochondrial ROS and developmental defects, indicating that ROS, mitochondrial division and development are critically interrelated processes.